Microscale Diffusion Properties of the Cartilage Pericellular Matrix Measured Using 3D Scanning Microphotolysis - Leddy, Holly A. (2008)
Chondrocytes (cartilage cells) are enclosed within a pericellular matrix (PCM) whose composition and structure differ from those of the extracellular matrix (ECM). Since the PCM surrounds each cell, molecules that interact with the chondrocyte must pass through the pericellular environment. A quantitative understanding of the diffusional properties of the PCM will help elucidate the PCM’s regulatory role in controlling transport to and from the chondrocyte. The diffusivity of a fluorescently-labeled 70 kDa dextran was quantified within the PCM of porcine articular cartilage using a newly-developed mathematical model of scanning microphotolysis (SCAMP). SCAMP is a rapid, line photobleaching method that accounts for out-of-plane bleaching attributable to high magnification. Data were analyzed by best-fit comparison to simulations generated using a discretization of the diffusion-reaction equation in conjunction with the microscope-specific three-dimensional excitation and detection profiles. The diffusion coefficient of dextran was significantly lower in the PCM than in the ECM in normal cartilage. In early-stage arthritic tissue, however, no significant differences in diffusivity were detectable. These results support the hypothesis that the diffusivity of the PCM is lower than that of the ECM, presumably due to differences in proteoglycan content, and that osteoarthritic changes in tissue affect the transport properties of the PCM.